Karst dangerous rock mass microorganism self-repairing reinforcing material and preparation method thereof
By developing self-repair and reinforcement materials for karst dangerous rocks, the problem of mismatch between traditional reinforcement materials and dolomite is solved, high strength, high durability and self-repair functions are achieved, and the stability of karst dolomite dangerous rocks is significantly improved. and security.
Patent Information
- Application Number
- CN202411432796.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
AI Technical Summary
Existing reinforcement materials cannot effectively predict and predict the collapse of dangerous rock mass of karst dolomite, and traditional materials do not match dolomite in terms of corrosion resistance, thermal expansion coefficient, elastic modulus and permeability, resulting in unfavorable bonding and coupling, reducing Reliability and long-term safety of reinforcement materials.
A self-healing and reinforcement material for karst dangerous rocks was developed. The reinforcement material made of high strength by reasonably proportioning gelling materials, dolomite powders, polymer materials, high-performance fibers, special bacterial species and gravy nutrient solution. , high durability and self-healing function, the permeability is less than that of dolomite, the thermal expansion coefficient is not much different from that of dolomite, and the elastic modulus is matched, which can automatically repair cracks after damage.
The stable reinforcement of dangerous rock mass of karst dolomite has been achieved, the overall strength and durability of the reinforcement material has been improved, the risk of further damage has been reduced, the safety has been enhanced, and the service life has been extended through the self-healing function.
Smart Images

Figure CN119263732A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of karst dangerous rock mass reinforcement materials, and in particular to a karst dangerous rock mass microbial self-repair reinforcement material and a preparation method thereof. Background Art
[0002] In domestic and foreign engineering examples and natural environments, there are a large number of karst landforms formed by chemical dissolution of karst rock bodies by water with dissolving power, supplemented by mechanical effects such as erosion, subsidence and collapse of flowing water. In particular, in southwest my country, there is one of the largest karst areas in the world, covering an area of about 540,000 km. 2 , mainly in Guangxi, Yunnan and Guizhou. Due to the special geological background and climatic conditions, the karst area has low soil-forming capacity, shallow and scattered soil layers; the surface and underground are dual structures, and surface water seeps a lot; plants are characterized by lithophytic and xerophytic, and the vegetation coverage rate is low. Therefore, rocks are very easy to further intensify weathering. In these areas, under the influence of various forces, a large number of dangerous karst rock bodies have been formed.
[0003] Karst dolomite dangerous rock bodies are the main type of dangerous rock bodies among karst dangerous rock bodies. These karst dolomite dangerous rock bodies often collapse and are destroyed suddenly, often causing great losses of personnel and property safety, and there are great safety hazards. The current technology is difficult to predict its occurrence and signs. A better solution is to use reinforcement materials for repair. However, some of the existing traditional reinforcement materials have many defects. For example, cement mortar is expensive, not environmentally friendly, and not corrosion-resistant. Resin rubber reinforcement materials have poor durability and corrosion resistance, and the strength cannot meet the requirements. In addition, the existing materials do not take into account that their thermal expansion coefficient is difficult to match with the widely existing dolomite in nature, so in the process of changing temperature in nature, large temperature stress will be generated; the elastic modulus is also different from the elastic modulus of the karst dolomite parent rock, and different degrees of deformation will occur when the large stress is generated by itself and the surrounding environment; the permeability is quite different from that of the dolomite parent rock, such as cement, resin, and rubber. The permeability is less than that of the parent rock, which will cause a large head difference between the interface of the repair material and the parent rock. All of the above reasons will have an adverse effect on the bonding coupling between the reinforcement material and the dangerous rock mass of dolomite in the karst area to varying degrees, reducing the reliability of the reinforcement material. At the same time, these materials cannot self-repair the dangerous rock mass that has been damaged by secondary development of cracks, thereby ensuring the long-term effectiveness and safety of the dangerous rock mass after repair. Summary of the invention
[0004] In order to solve the above-mentioned problems, the present invention provides a karst dangerous rock mass microbial self-repair reinforcement material and a preparation method for dolomite dangerous rock mass. Through reasonable material ratios, the reinforcement material has high strength, high durability, corrosion resistance and self-repair functions. At the same time, the permeability of the material of the present invention is lower than that of the dolomite dangerous rock mass, the thermal expansion coefficient is not much different from that of the dolomite dangerous rock mass, and the elastic modulus is well matched with the dolomite dangerous rock mass, which provides an efficient and reliable solution for the stable reinforcement of karst dolomite dangerous rock mass. Specifically, the durable and compatible self-repair reinforcement material for dolomite dangerous rock mass in karst areas of the present invention comprises the following steps:
[0005] Step 1: Statistically analyze the components of dolomite dangerous rock bodies in different karst areas. Statistics show that dolomite is the main component, accounting for more than 50%, between 50% and 90%. For example, pure dolomite, mud-bearing dolomite, silicon-bearing dolomite, organic dolomite, and replaced dolomite are doped with about 40% calcite, about 20% quartz, about 15% feldspar, and about 10% clay minerals. The particle size distribution, porosity, and density of different dolomites are measured.
[0006] Step 2: Determine the physical, mechanical and chemical properties of different parent rocks, prepare standard cylindrical and cubic specimens of parent rocks, and measure the parent rock tensile strength σ by Brazilian splitting test. t , the parent rock cube specimen was taken to measure the parent rock shear strength τ0 through indoor direct shear test, and the parent rock cylinder specimen was taken to conduct indoor accelerated aging test and then measure its aging damage tensile strength σ dt To measure its durability, the parent rock cylinder specimens were taken and tested at different P H The corrosion damage tensile strength σ was measured after immersion in hydrochloric acid solution for t2 time. dc In order to measure its corrosion resistance, a parent rock cube specimen is dried and weighed m0, placed in a vacuum barrel for vacuum immersion for t3 time until it is completely saturated and weighed m1, the parent rock porosity e0 is calculated, and the permeability P0 is calculated using the existing formula. The parent rock cube specimen is subjected to a uniaxial compression test to obtain a uniaxial compression stress-strain curve, and its straight line segment is taken. The parent rock elastic modulus E0 is calculated using the relationship between the elastic modulus and the stress-strain curve. The parent rock cube specimen is installed with a strain gauge and placed in a constant temperature box for heating to measure the linear thermal expansion coefficient K0 of the rock.
[0007] Step 3, based on the physical and mechanical properties, chemical properties of dolomite parent rock and some existing correlation studies, it is preliminarily determined that the various components of the reinforcement material of the present invention are: gelling material, dolomite powder, polymer material, admixture, high-performance fiber, special strains, and meat juice nutrient solution (prepared at a ratio of 3.0 g beef extract, 10.0 g peptone, and 5.0 g NaCl per liter of water);
[0008] Step 4, referring to the existing relevant research, combined with the relevant characteristics of dolomite parent rock, select appropriate components and preliminarily determine the approximate range of the content of each component of the reinforcement material: the content of cementitious materials accounts for 18% to 30% of the total mass; dolomite powder developed from parent rock is selected as aggregate to ensure that the reinforcement material has good compatibility with the dangerous rock, and the content of dolomite powder accounts for 45% to 65% of the total mass; the content of polymer materials accounts for 1% to 5% of the total mass; the content of admixtures accounts for 3% to 7% of the total mass; the content of high-performance fibers accounts for 3% to 7% of the total mass; the content of special bacteria accounts for 1% to 5% of the total mass, and the addition of gravy nutrient solution provides nutrients required for the growth of microbial agents, and the content accounts for 1% to 5% of the total mass;
[0009] Step 5: To determine the specific composition and ratio of the reinforcement materials, a self-repair reinforcement material composition scheme with different levels of multiple factors is designed according to the uniformity test requirements, and a specific test scheme is designed according to the uniformity design test scheme principle;
[0010] Step 6: Prepare the reinforcement material slurry according to the above ratios, and cast multiple groups of cubic specimens and cylindrical specimens respectively. It should be noted that specimens with different ratios should be clearly marked to avoid confusion in later tests. In addition, the parent rock cubic specimen is cut along the central cross section to artificially create a fractured dangerous rock mass to ensure that the experimental variables are as uniform as possible. The prepared reinforcement material is used to repair the dangerous rock mass, and these specimens are placed in the same standard curing environment for curing time t1;
[0011] Step 7: Testing the performance of the reinforcement material. The present invention provides the following specific solutions:
[0012] Tensile strength test at different ages: Brazilian splitting test was performed on cylindrical specimens cured at different ages under standard conditions, and their early and middle strength σ mt ;
[0013] Durability test: Take the standard cylindrical specimen of the reinforced material and place it in an indoor accelerated aging test chamber for accelerated aging. The device can realize freeze-thaw cycles, dry-wet cycles, and ultraviolet irradiation to accelerate the aging effect of the material on the simulated natural environment. Take the specimen after the damage time t4 to conduct the Brazilian splitting test to measure its aging damage tensile strength σ mdt ;
[0014] Corrosion resistance test: Take the reinforced material cylindrical specimen and immerse it in hydrochloric acid solution of different concentrations for t2 time. During the immersion process, measure the solution P every certain time. H , timely adjust the solution P H Make it meet the requirements and record; take the acid-treated specimens for Brazilian splitting test to measure its corrosion damage tensile strength σ mdc ;
[0015] Interface compatibility test: Take the prepared reinforcement material repair and maintenance specimens, conduct indoor direct shear tests, and measure their interface shear strength; it is worth noting that when conducting the shear test, the test must be stopped immediately after the specimen reaches the peak strength. At this time, well-developed cracks have been generated in the specimen without large through cracks, so as to facilitate the subsequent self-repair performance verification;
[0016] Self-repairing performance test: After the above shear test, the specimens were cured for t3 time, and then the indoor direct shear test was carried out again to measure the self-repairing shear strength τ hr ;
[0017] Permeability test: water absorption is used to characterize its permeability, which simplifies the test process and has high reliability. The specific method is to take a cubic curing specimen of the reinforcement material and dry it, and measure the dry mass of the reinforcement material m m0 , placed in a vacuum barrel for vacuum immersion, weighed after t3 time m m1 The porosity e m , the permeability P is obtained by formula conversion m ;
[0018] Elastic modulus test: Take a cubic specimen of the reinforcement material and perform a uniaxial compression test. According to its stress-strain curve, take its straight line segment and use the relationship between the elastic modulus and stress-strain to calculate the elastic modulus E of the reinforcement material. m ;
[0019] Linear thermal expansion coefficient test: Take a cubic specimen of reinforcement material, select three mutually perpendicular faces, install strain gauges on it along the 45° direction, place it in a constant temperature box and heat it to a certain temperature to measure the strain of the rock, and calculate the linear thermal expansion coefficient K m ;
[0020] Step 8: Based on the data obtained in step 7, the following indicators are given to verify whether they meet the requirements:
[0021] Strength indicators at different ages: where σ mti The tensile strength of the reinforcement materials at different curing ages is shown in order;
[0022] Durability index:
[0023] Corrosion resistance index: Where i represents different P H The tensile strength of corrosion damage of the reinforcement material or parent rock after being immersed in hydrochloric acid solution for t2;
[0024] Interface compatibility index:
[0025] Self-healing indicators: where τ hrti The shear strength of the specimens repaired with reinforcement materials at different ages of secondary curing are shown in order;
[0026] Permeability index: in P is the permeability of the corresponding specimen, e is the porosity of the corresponding specimen, and V is the volume of the corresponding specimen;
[0027] Elastic modulus index: in
[0028] Linear thermal expansion coefficient index: in ε is the corresponding linear strain, L is the side length of the corresponding cubic specimen, and T is the elevated temperature;
[0029] Step 9: Based on the above data processing, select the best ratio that meets various indicators within the test range;
[0030] Through the karst dangerous rock microbial self-repair reinforcement material and preparation method of the present invention, effective reinforcement and self-repair of karst dolomite dangerous rock can be achieved. The components in the reinforcement material work together to improve the performance of the reinforcement material. At the same time, the reasonable ratio enables the reinforcement material to have a self-repair function while maintaining high strength and durability, thereby extending the service life of the reinforcement material. It should be noted that the specific implementation method of the present invention can be adjusted and optimized according to actual engineering needs, and the proportion of each component can be adjusted according to factors such as the specific conditions of the dangerous rock, reinforcement requirements, and construction environment to adapt to different engineering conditions and requirements. In short, the present invention provides a durable and compatible self-repair reinforcement material and preparation method for karst dolomite dangerous rock, which has significant practical value and broad application prospects. Through the introduction of reasonable material ratios and self-repair mechanisms, the reinforcement material provides an efficient and reliable solution for the stable reinforcement of karst dolomite dangerous rock.
[0031] The present invention has at least the following technical effects or advantages:
[0032] The present invention provides a karst dangerous rock microbial self-repair reinforcement material and preparation method, which have significant technical effects and many advantages. First, the present invention makes full use of the similarity between dolomite powder and karst dolomite dangerous rock composition to achieve good compatibility. This compatibility not only enhances the bonding force between the reinforcement material and the dangerous rock, but also effectively improves the overall stability and significantly reduces the risk of further damage to the dangerous rock. Secondly, the epoxy resin used has excellent bonding strength, chemical corrosion resistance and good mechanical properties, which can effectively improve the overall strength and durability of the reinforcement material. Through the synergistic effect with components such as silicate cement and dolomite powder, a solid reinforcement layer is formed to enhance the stability of the dangerous rock. More importantly, through the synergistic effect of microbial agents and nutrient solution, the reinforcement material can automatically repair cracks and pores after damage occurs, thereby enhancing its safety and reducing maintenance costs. In addition, the preparation method of the present invention is simple and easy, and the required materials are easy to obtain, which is convenient for promotion and application in actual engineering. At the same time, through the optimization and adjustment of the material ratio, it can adapt to different geological conditions and engineering requirements to achieve personalized reinforcement schemes. In summary, the durable compatible self-repairing reinforcement material for karst dolomite dangerous rock mass and the preparation method thereof provided by the present invention have excellent performance and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a flow chart of the durable compatible self-repairing reinforcement material for karst dolomite dangerous rock mass and its preparation method of the present invention;
[0034] Figure 2 This is a research scheme diagram of the durable compatible self-repairing reinforcement material and preparation method for karst dolomite dangerous rock mass of the present invention; DETAILED DESCRIPTION
[0035] The following is a description of a preparation method of a microbial self-repairing reinforcement material for karst dangerous rock mass in accordance with the present invention by taking the repair of a dolomite dangerous rock mass in a karst area as an example in conjunction with the accompanying drawings. The following examples are exemplary and intended to be used to explain the preparation method, and should not be construed as limiting the present invention.
[0036] The present invention provides a specific implementation method of a durable and compatible self-repairing reinforcement material for karst dolomite dangerous rock mass and a preparation method. The following are the detailed steps and operation flow:
[0037] Step 1: Analyze the various components of the dolomite dangerous rock mass in this karst area. Statistics show that dolomite is the main component, accounting for 67.4%, doped with 13.4% quartz, 17.7% calcite and 1.5% clay minerals, and measure its average particle size d through physical experiments. p , density ρ, porosity e0;
[0038] Step 2: Determine the physical, mechanical and chemical properties of the parent rock, prepare standard cylindrical and cubic specimens of the parent rock (cylinder: 50 mm diameter, 100 mm height, cube: side length 100 mm), and measure the parent rock tensile strength σ by the Brazilian splitting test. t , the parent rock cube specimen was taken to measure the parent rock shear strength τ0 through indoor direct shear test, and the parent rock cylinder specimen was taken to conduct indoor accelerated aging test and then measure its aging damage tensile strength σ dt To measure its durability, the parent rock cylinder specimens were taken for P H The samples were immersed in hydrochloric acid solution with concentrations of 7, 6, 5, 4, and 3 for 30 days, and then the tensile strength of corrosion damage was measured. dc To measure its corrosion resistance, take the parent rock cube specimen, dry it and weigh it m0, place it in a vacuum barrel and soak it in vacuum for one week, and then weigh it m1 to measure its permeability after it is completely saturated. Take the parent rock cube specimen for uniaxial compression test to obtain the uniaxial compression stress-strain curve, take its straight line segment, and calculate the parent rock elastic modulus E0 using the relationship between elastic modulus and stress-strain. Take the parent rock cube specimen, install the strain gauge, place it in a constant temperature box and heat it up to measure the linear thermal expansion coefficient K0 of the rock. Table 1 Physical property parameters of dolomite parent rock Table 2 Mechanical properties of dolomite parent rock (MPa)
[0039] Step 3, based on the physical and mechanical properties, chemical properties of dolomite parent rock and some existing correlation studies, it is preliminarily determined that the components of the reinforcement material of the present invention are: silicate cement, water glass, dolomite powder, epoxy resin, silicate, polyester fiber, pasteurella sporangium, and meat juice nutrient solution;
[0040] Step 4: Refer to the existing relevant research, combine the relevant characteristics of dolomite parent rock, select appropriate components and preliminarily determine the approximate range of the content of each component of the reinforcement material: the main cementitious material is silicate cement, which accounts for 17% to 25% of the total mass; water glass is added to improve the performance of the reinforcement material, and its content accounts for 1% to 5% of the total mass; dolomite powder developed from parent rock is selected as aggregate to ensure that the reinforcement material has good compatibility with the dangerous rock, and the content of dolomite powder accounts for 45% to 65% of the total mass; epoxy resin is added to improve the performance of the reinforcement material, and the content of dolomite powder accounts for 45% to 65% of the total mass. Improve the overall strength and durability of the reinforced material, with a content of 1% to 5% of the total mass; add silicate to improve the corrosion resistance of the material, with a content of 3% to 7% of the total mass; add polyester fiber to improve the tensile strength and toughness of the reinforced material, with a content of 3% to 7% of the total mass; add pasteurian cysts Sarcina powder to achieve the self-repair function of the reinforced material through its microbial induced calcification crystallization, with a content of 1% to 5% of the total mass; add nutrient solution to provide nutrients required for the growth of microbial agents, with a content of 1% to 5% of the total mass;
[0041] Here is how biologically induced calcification works: CO(NH2)2+2H2O→H2CO3+2NH3
[0042] Step 5: To determine the specific composition and ratio of the reinforcement materials, a self-repair reinforcement material composition scheme with different levels of multiple factors is designed according to the uniformity test requirements, and a specific test scheme is designed according to the uniformity design test scheme principle; Table 3 Design level of reinforcement materials (hereinafter all are mass ratios) Table 4 Uniform design level of reinforcement materials (hereinafter all are mass ratios)
[0043] Step 6: Prepare the reinforcement material slurry according to the above ratios, and cast multiple groups of cubic specimens and cylindrical specimens respectively. It should be noted that specimens with different ratios should be clearly marked to avoid confusion in later tests. In addition, the parent rock cubic specimen is cut along the central cross section to artificially create a fractured dangerous rock mass to ensure that the experimental variables are as uniform as possible. The prepared reinforcement material is used to repair the dangerous rock mass, and these specimens are placed in the same standard curing environment for curing for 25 hours.
[0044] Step 7: Testing the performance of the reinforcement material. The present invention provides the following specific solutions:
[0045] Tensile strength test at different ages: Brazilian splitting test was performed on cylindrical specimens cured for 1 day, 5 days, 10 days, 15 days, 20 days and 25 days, and their early and middle strength σmt ; Table 5 Early and mid-term strength of reinforcement materials (MPa)
[0046] Durability test: Take the standard cylindrical specimen of the reinforced material and conduct accelerated aging in an indoor accelerated aging test chamber. The device can realize freeze-thaw cycle, dry-wet cycle, and ultraviolet irradiation to accelerate the aging effect of the material in the simulated natural environment. Take the specimen 30 days after damage and conduct the Brazilian splitting test to measure its aging damage tensile strength σ mdt ; Table 6 Durability damage tensile strength σ of reinforcement materials mdt (MPa)
[0047] Corrosion resistance test: Take the reinforced material cylindrical specimens and immerse them in hydrochloric acid solutions of different concentrations for 30 days. During the immersion process, measure the solution P every 12 hours. H , timely adjust the solution P H Make it meet the requirements and record; take the acid-treated specimens for Brazilian splitting test to measure its corrosion damage tensile strength σ mdc , and through the formula Assess whether the corrosion resistance of the reinforcement material meets the requirements; Table 7 30-day corrosion damage tensile strength σ of reinforced materials mdc (MPa)
[0048] Interface compatibility test: Take the prepared reinforcement material repair and maintenance specimens, conduct indoor direct shear tests, and measure their interface shear strength; it is worth noting that when conducting the shear test, the test must be stopped immediately after the specimen reaches the peak strength. At this time, well-developed cracks have been generated in the specimen without large through cracks, so as to facilitate the subsequent self-repair performance verification; Table 8 Interface shear strength τ of reinforcement materials h (MPa)
[0049] Self-repairing performance test: After the above shear test, the specimens were cured again for different time periods, and then the indoor direct shear test was conducted again to measure the self-repairing shear strength τ hr ; Table 9 Repair time of reinforcement materials Self-repair shear strength τ hr (MPa)
[0050] Permeability test: water absorption is used to characterize its permeability, which simplifies the test process and has high reliability. The specific method is to take a cubic curing specimen of the reinforcement material and dry it, and measure the dry mass of the reinforcement material m m0 , placed in a vacuum barrel for vacuum soaking, weighed after one week m1 Measure its saturated mass, calculate its porosity, and convert it into permeability through the formula; Table 10 Saturated mass of reinforcement materials m m1 And dry mass m m0 (g)
[0051] Elastic modulus test: Take a cubic specimen of the reinforcement material and perform a uniaxial compression test. According to its stress-strain curve, take its straight line segment and use the relationship between the elastic modulus and stress-strain to calculate the elastic modulus E of the reinforcement material. m ;
[0052] Linear thermal expansion coefficient test: Take a cubic specimen of reinforcement material, select three mutually perpendicular faces, install strain gauges on it along the 45° direction, place it in a constant temperature box and heat it to a certain temperature to measure the strain of the rock, and calculate the linear thermal expansion coefficient K m ;
[0053] Step 8: Based on the data obtained in step 7, the following indicators are given to verify whether they meet the requirements:
[0054] Strength indicators at different ages: where σ mti The tensile strength of the reinforcement materials at different curing ages is shown in order;
[0055] Durability index:
[0056] Corrosion resistance index: Where i represents different P H The tensile strength of corrosion damage of the reinforcement material or parent rock after immersion in hydrochloric acid solution for 30 days;
[0057] Interface compatibility index:
[0058] Self-healing indicators: where τ hrti The shear strength of the specimens repaired with reinforcement materials at different ages of secondary curing are shown in order;
[0059] Permeability index: in P is the permeability of the corresponding specimen, e is the porosity of the corresponding specimen, and V is the volume of the corresponding specimen;
[0060] Elastic modulus index: in
[0061] Linear thermal expansion coefficient index: in ε is the corresponding specimen linear strain, L is the corresponding cubic specimen side length, and T is the temperature rise of the thermostat;
[0062] Step 9: Based on the above data, the best ratio within the test range can be calculated as follows: Table 11 Optimal ratio of reinforcement materials within the experimental range (the following are all mass ratios)
Claims
1. A method for preparing a karst dangerous rock mass microbial self-repair reinforcement material, characterized in that: The following steps are involved: Step 1: Statistically analyze the composition of dangerous dolomite bodies in different karst areas, such as pure dolomite, mud-bearing dolomite, silicon-bearing dolomite, organic-bearing dolomite, and replaced dolomite, and measure the particle size distribution, porosity, and density of different dolomites; Step 2: Determine the physical, mechanical and chemical properties of the parent rock, prepare standard cylindrical and cubic specimens of the parent rock, and measure the parent rock tensile strength σ by using the Brazilian splitting test on the cylindrical specimens of the parent rock t , the parent rock cube specimen was taken to measure the parent rock shear strength τ0 through indoor direct shear test, and the parent rock cylinder specimen was taken to conduct indoor accelerated aging test and then measure its aging damage tensile strength σ dt To measure its durability, the parent rock cylindrical specimens were immersed in hydrochloric acid solutions of different pH values for t2 time, and their corrosion damage tensile strength σ was measured. dc , take a cube of parent rock and dry it, weigh it m0, place it in a vacuum barrel and soak it for t3 time until it is completely saturated, then weigh it m1, and use the formula The permeability of the parent rock P0 is calculated, and a uniaxial compression test is performed on a parent rock cube specimen to obtain a uniaxial compression stress-strain curve. The straight line segment is taken and the relationship between the elastic modulus and the stress-strain is used to calculate the elastic modulus E0 of the parent rock. The parent rock cube specimen is installed with a strain gauge and placed in a medium temperature rise to measure the linear thermal expansion coefficient K0 of the rock. Step 3: Based on the physical and mechanical properties, chemical properties of dolomite parent rock and some existing correlation studies, the main components of the reinforcement materials are preliminarily determined to be: cementitious materials, dolomite powder, polymer materials, admixtures, high-performance fibers, special strains, and nutrient solution; Step 4: Refer to existing relevant research and combine the relevant characteristics of dolomite parent rock to select appropriate components and preliminarily determine the approximate range of the content of each component of the reinforcement material; Step 5: To determine the specific composition and ratio of the reinforcement materials, a self-repair reinforcement material composition scheme with different levels of multiple factors is designed according to the uniformity test requirements, and a specific test scheme is designed according to the uniformity design test scheme principle; Step 6: Prepare the reinforcement material slurry according to the above ratios, and cast multiple groups of cubic specimens and cylindrical specimens respectively, mark the specimens with different ratios, and cut the parent rock cubic specimen along the central cross section to artificially create a fractured dangerous rock model, take the prepared reinforcement material to fill the cracks of the fractured dangerous rock model, and place these specimens in the same curing environment for curing time t1; Step 7: The performance test of the karst dangerous rock microbial self-repair reinforcement material, the present invention proposes a systematic, comprehensive, multi-standard experimental scheme, as follows: Tensile strength test at different ages: Brazilian splitting test was performed on cylindrical specimens cured at different ages under standard conditions, and the tensile strength σ at different ages was recorded. mt ; Durability test: Take the reinforced material cylindrical specimens and accelerate the aging in the indoor accelerated aging test box. The device can realize freeze-thaw cycle, dry-wet cycle, and ultraviolet irradiation to accelerate the aging damage of the material by simulating the natural environment. Take the specimens after t4 time and perform the Brazilian splitting test to measure their aging damage tensile strength σ mdt ; Corrosion resistance test: Take the cylindrical specimens of the reinforcement material and immerse them in hydrochloric acid solutions of different concentrations for t2 time. During the immersion process, measure the solution pH at regular intervals, and adjust the solution pH in time to meet the requirements and record them. Take the acid-treated specimens and conduct the Brazilian splitting test to measure their corrosion damage tensile strength σ mdc ; Interface compatibility test: Take the prepared reinforcement material repair and maintenance specimens and conduct indoor direct shear tests to measure their interface shear strength; when conducting shear tests on crack filling specimens, the test must be stopped immediately after the specimens reach the peak strength. At this time, the specimens have well-developed cracks but no large through cracks, so as to facilitate subsequent self-repair performance verification; Self-repairing performance test: Take the specimen after the above shear test, and after curing for t4 hours under the same conditions, conduct indoor direct shear test to measure its self-repairing shear strength τ hr ; Permeability test: water absorption is used to characterize its permeability, which simplifies the test process and has high reliability. The specific method is to take the cubic specimen of reinforcement material and fully dry it in a constant temperature box to measure the dry mass m of the reinforcement material. m0 , placed in a vacuum barrel and soaked for t3 time, then weighed m m0 The porosity is measured and the permeability P is calculated by the formula m ; Elastic modulus test: Take a cubic specimen of the reinforcement material and perform a uniaxial compression test. According to its stress-strain curve, take its straight line segment and use the relationship between the elastic modulus and stress-strain to calculate the elastic modulus E of the reinforcement material. m ; Linear thermal expansion coefficient test: Take a cubic specimen of reinforcement material, select three mutually perpendicular faces, and ° The strain gauge is installed in the direction and placed in a constant temperature box. After heating to a certain temperature, the strain of the rock is measured and the linear thermal expansion coefficient K can be calculated. m ; Step 8: Based on the data obtained in step 7, the present invention proposes theoretical calculations of different indicators to verify whether the performance of the karst dangerous rock microbial self-repair reinforcement material meets the requirements: Strength indicators at different ages: where σ mti The tensile strength of the reinforcement materials at different curing ages is shown in order; Durability index: Corrosion resistance index: Where i represents the tensile strength of corrosion damage of the reinforcement material or parent rock after being immersed in hydrochloric acid solutions of different pH values for t2; Interface compatibility index: Self-healing indicators: where τ hrti The shear strength of the specimens repaired with reinforcement materials at different ages of secondary curing are shown in order; Permeability index: in P is the permeability of the corresponding specimen, d p is the average particle diameter of the specimen, e is the porosity of the corresponding specimen, and V is the volume of the corresponding specimen; Elastic modulus index: in Linear thermal expansion coefficient index: in ε is the corresponding linear strain, L is the side length of the corresponding cubic specimen, and T is the elevated temperature; Step 9: Based on the above data processing, select the best ratio that meets various indicators within the test range.
2. The reinforcement material formula obtained according to the method for preparing a karst dangerous rock microbial self-repair reinforcement material according to claim 1 is characterized in that: The nutrient solution is a meat juice nutrient solution prepared according to the ratio of 3.0g beef extract, 10.0g peptone and 5.0g NaCl per liter of water.
3. The reinforcement material formula obtained according to the method for preparing a karst dangerous rock microbial self-repair reinforcement material according to claim 1 is characterized in that: The components of the reinforcement material are silicate cement, water glass, dolomite powder, epoxy resin, silicate, polyester fiber, pasteurized Sarcina powder, and gravy nutrient solution; the component ratios of the reinforcement material are: bone glue ratio 1.7, water glass cement ratio 0.16, epoxy resin colloid ratio 0.18, silicate colloid ratio 0.32, polyester fiber colloid ratio 0.26, bacterial powder colloid ratio 0.006, nutrient solution colloid ratio 0.26, and water-cement ratio 0.73.